Bruka utan att förbruka - när andra intressen än ekonomin får styra - Sandström, Elin (2014)
To have a forest area close to the city is of great importance for the city population’s well being. Children develop their motor skills, concentration and imagina-tion and the adults have a place to shake of the stress from work. Forest areas are used to exercise at, play in and to find a moment of peace and silence.